Analisa ekonomi budidaya kerapu macan (Epinephelus fuscoguttatus) dan kerapu bebek (Cromileptes altivelis) dalam keramba jaring apung di Indonesia - Farok Afero (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. This study presents an economic analysis of tiger and humpback grouperat different production scales in Indonesia. The results highlight the nonviabilityof small scale tiger grouper, with a 5 years projected negativecumulative cash flow of Rp. 18.102.650 and a negative net present value (NPV)of Rp. 22.059.576. An increasing production scale of tiger grouper highlight amarginal viability for medium scale (with a 5 year projected cumulative cashflow of Rp. 198.320.673 and a positive NPV of Rp. 105.578.440; with a benefitcost ratio of 1,25; an internal rate of return (IRR) of 88%; and a paybackperiod of 0,99 year), and an economically viable of large scale cage culture(with a 5 year projected cumulative cash of Rp. 707.746.923; a NPV of Rp.406.801.749; a benefit cost ratio of 1,33;an internal rate of return of 157%;and a payback period of 0,57 year). The economic analysis of humpback grouper atdifferent production scales highlight positive cumulative cash, a positive NPV,a benefit cost ratio higher than 2, an internal rate of return over 300% and apayback period of less than one year. A sensitivity analysis revealed thatincreased survival rate up to 80% would increase cumulative cash and NPV ofsmall scale tiger grouper cage culture. Additionally, improved profitabilityperformance was associated with decreased major production costs, increasedproduction and price of the product.Situs barbarslot terpercaya dengan berbagai pilihan permainan seru, peluang menang besar, dan fitur bonus menarik. Nikmati pengalaman bermain aman dan menyenangkan kapan saja!Barbarslot adalah salah satu situs resmi https://www.26barsandaband.com/videos/, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025.Nikmati pengalaman bermain https://www.carsoncityantiquemall.com/contact-3, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan.Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu!Situs gacorqq adalah game yang sering memberikan kemenangan besar, meskipun hasilnya tetap acak, tak bisa diprediksi, dan bergantung pada keberuntungan pemain.Tempat terbaik hari ini untuk bermain game slot, dengan beragam permainan tersedia cukup dengan minimal deposit 5000 di situs gacorqq login, Anda dapat bermain sepuasnya dan kapan saja.Hadir untuk Anda slot deposit 5000, bersama situs gacor5000 raih kemenenangan mudah dan juga fasilitas game terlengkap beda dari lainnya.kumolojoyohttps://pn-batang.go.id/id/https://www.ppdkk.edu.my/https://cyclinic.com.tw/https://carriesbridalcollection.com/https://inspimate.co.ke/https://www.affluence-inf.com/https://socialmovementtechnologies.org/https://www.dac-hr.com/https://ican4ir.com/https://ucrnn.net/https://family-life.co/https://pelangideco.com/https://elsekgroup.com/https://icanleaduganda.com/https://lowveldfruits.co.za/https://dominionng.com/https://www.lwuc.org/https://acadasuite.com/https://noraktech.com/https://burocromatico.mx/https://norakle.com/https://downeyrootcanal.com/https://www.summit-smile.com/https://www.mycreativesmiles.com/https://appetito.uz/https://adsec.net/https://fahariloungemalindi.com/https://dahnanproperties.com/https://foresthydrology.gov.bc.ca/https://www.gebhardtforcolorado.com/https://gitlab.weather.noaa.gov/https://msoid.abom.org/https://www.rogeebeverlyhills.com/https://wasre-datamover.umaryland.edu/https://worthyfigures.com/https://www.helsingborgsakademin.helsingborg.se/https://saa.uinsgd.ac.id/https://designsbylillianj.com/https://www.tsv-einheit.de/https://starbuckspartnerhoursinfo.com/https://infosphereeducation.com/https://amandlaomnotho.com/https://puntacanard.do/https://alessandraquartaconte.com/https://sieudaga.com/https://horusservices.com.co/https://tiffanyqueen.store/https://accessstudentportal.com/https://www.fitlifefoundations.com/https://www.nukandy.com/https://filipinofoodcart.com/https://starbridgeguides.com/https://3beansart.com/https://www.iestpahtsihuas.edu.pe/https://worldoffoods.net/https://abejotaburnaby.cl/https://peoplesopioidsummit.com/https://voordeliggenieten.nl/https://bewealthyandjoyful.com/https://fabiananliker.com/https://ipracticegolf.com/https://lhbtiqontact.nl/https://maxdiscountcodes.com/https://stturtle.com/https://clickcatalystai.com/https://grubz.co.za/https://ir-terrasverwarming.nl/https://refael-group.co.il/https://www.thedriftlesssheep.com/https://yabolichina.com/https://www.gr4nt.com/https://moviestylepopcorn.com/https://pcavisen.dk/https://emersonart.com/https://surfessay.com/https://tuaton.com/https://chelsea-westside.com/https://jadejewlery.com/https://sencesecret.com/https://www.passticks.com/https://detucasa.online/https://davidrefael.co.il/https://refaelgroup.co.il/https://verygoodclean.com/https://www.knightvisor.com/https://klinkerhaus-am-wald.de/https://medicata.ee/https://refael-nadlan.co.il/https://www.bajioffer.com/https://buycyh.com/https://giuseppemagra.com/https://www.kutivzkouture.co.uk/https://lenyvankessel.nl/https://the-domains.com/https://thenativeborne.com/https://windowsandoors.co.uk/https://max-aperture.com/https://www.tacology101.com/https://paragontelco.com/https://dataleaked.com/https://brassringlineage.co/https://capelsoundhaven.com.au/https://goldcoastmecfs.com/https://sbtienda.com/https://shehealth.com/https://worldofteas.ca/https://mamieexcels.com/https://patriotluxpools.com/https://cascadesculinary.com/https://texasprideconcrete.com/https://recipetohappy.com/https://laalquiladora.com/https://thevpsacademy.com/https://ministry-websites.com/https://businesswebsiteservices.net/https://sqrealty.com.mx/https://emrooznama.com/https://hubbil.com/https://seoactions.com/https://testlang.com/https://thevinenetwork.com/https://yogaconmarcella.com/https://lakehouseufaula.com/https://elliotpro.com/https://nftgallerycenter.com/https://eastexhomecenter.com/https://culturallyresponsiveminds.com/https://leadgeeks.net/https://nextwavestrategies.ai/https://naju.us/https://roofingmasters.ca/https://smokemart.ca/https://www.maquette.ca/https://www.caraccidentattorneycolumbia.com/https://www.ergotijm.nl/https://www.earthyoga.store/https://acesdrains.com/https://agentedesegurosdesalud.com/https://asportdesigns.com/https://astatic-solutions.com/https://beattiepropertyservices.com/https://bigwestgiftsuite.com/https://bleroofing.com/https://bmugc.com/https://cardsandcrime.com/https://dharmasimple.com/https://ebolightmd.com/https://anovelidea.com.au/https://calvaryhill-lyman.org/https://eficon.cl/https://divinorigen.cl/https://einsparhelden.de/https://bulkbuydirect.store/https://www.caedenfetters.com/https://www.duncandigital.com/https://elixirclio.com/